Review of the Development of the Concept of Ericson's Personality Psychology Theory in Physical Education Learning for Elementary School Children - Waffak, Muhammad Nasihul; Taryatman (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2024)
Psychosocial Theory by Erik H. Erikson and Psychosexual Theory by Sigmund Freud. Freud introduced the school of psychoanalysis, which was further developed by Erikson into Psychosexual Theory and then Psychosocial Theory. In his book "Childhood and Society," Erikson compiled "The Eight Stages of Human Development" to explain the psychosocial process of ego development. Erikson outlined eight stages of human development from infancy to old age, following the epigenetic principle that human personality develops through these eight stages. Erikson is known for his efforts to develop this theory, which is an extension of Freud's theory, which focuses more on adolescence.